Vernacular wisdom: the basis of formulating compatible living environment in Oman - Abdul Majid, Noor Hanita; Shuichi, Hokoi; Takagi, Nozomi (Elsevier, 2012)
Vernacular architecture has been accepted as a product that has its roots both in culture and climate. This paper examines the architectural elements of Omani houses to outline the responses towards culture and climate by analysis of house samples and survey responses. The survey gathered data on the attitude and behavior of the inhabitants with evidences of set point temperature, operating hours and thermal sensation. The results of the analysis on design parameters of vernacular and contemporary houses and the current behavior and attitude of occupants suggested the basis of formulating compatible living environment in Oman.